2009
DOI: 10.1167/iovs.08-1882
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Lactoferrin Stimulates Human Corneal Epithelial Alkali Wound Healing In Vitro

Abstract: These results suggest that BLF at >or=2.5 mg/mL stimulates HCLE wound healing, and this stimulation is mediated through the upregulation of PDGF or IL-6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 42 publications
1
22
0
1
Order By: Relevance
“…However, while the previous study indicated the LF-induced increase in goblet cell density, we did not observe any differences in expression of goblet cell-related genes (mucin1, mucin4, mucin5AC, and SAM pointed domain containing ets transcription factor) between the control and the LF experimental group (data not shown). Further investigation of LF-containing eye drops is necessary to confirm their presumed goblet cell increasing effect [23], [24] and the consequent improvement in the ocular surface epithelium condition [17], [25], [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, while the previous study indicated the LF-induced increase in goblet cell density, we did not observe any differences in expression of goblet cell-related genes (mucin1, mucin4, mucin5AC, and SAM pointed domain containing ets transcription factor) between the control and the LF experimental group (data not shown). Further investigation of LF-containing eye drops is necessary to confirm their presumed goblet cell increasing effect [23], [24] and the consequent improvement in the ocular surface epithelium condition [17], [25], [26].…”
Section: Discussionmentioning
confidence: 99%
“…BLf was also described to promote hyaluronan synthesis in normal human dermal fibroblasts by increasing hyaluronan synthase 2 [170], suggesting that Lf-stimulated wound healing could be related to up-regulation of hyaluronan. In corneal epithelial wound healing, bLf promotes wound closure in human corneal epithelial cells [171].…”
Section: Lactoferrin Anti-cancer Activity: Inhibition Of Cell Migratimentioning
confidence: 99%
“…18 LF promotes corneal wound healing after alkali-burn injury in mice 19 and epithelial regrowth in the in vitro studies of monolayers of corneal epithelial cells. 20,21 Using a laser-induced choroidal neovascularization murine model, we were able to demonstrated that the endogenous LF provides noticeable protection from choroidal neovascularization lesions in WT mice compared to LF knockout (LFKO) mice. Furthermore, treatment of LFKO mice with exogenous LF reduced choroidal neovascularization lesions.…”
Section: Introductionmentioning
confidence: 96%